Perceived discrimination is associated with poorer health and well‐being outcomes among Pacific peoples in New Zealand. (16th August 2019) - Kapeli, Sarah A.; Manuela, Sam; Sibley, Chris G.
Abstract: Our study investigated the association between perceived discrimination and outcomes related to health and well‐being for Pacific adults in New Zealand. We examined personal and group discrimination from the 2013 wave of the New Zealand Attitudes and Values Study ( n = 429 women and 196 men). Personal discrimination was associated with poorer health and well‐being outcomes (higher psychological distress and lower self‐esteem, subjective evaluation of health, satisfaction with life and personal well‐being). Group discrimination, in contrast, was associated with poorer well‐being but not health outcomes (lower subjective evaluation of health and personal well‐being). These findings corroborate previous research and highlight the corrosive effect of discrimination towards health and well‐being among Pacific communities in New Zealand.